A comparative study on the application effects of total laparoscopic right-sided colon anastomosis and laparoscopic plus auxiliary incision anastomosis in radical resection of right-sided colon cancer - He Zhiyong; Qi Sheng; Zeng Dong; Zhang Jiancheng (结直肠肛门外科)
[Objectives] To compare the application effects of total laparoscopic right-sided colon anastomosis and laparoscopic plus auxiliary incision anastomosis in radical resection of right-sided colon cancer (RCC). [Methods] A retrospective analysis was conducted on the clinical data of 103 patients with RCC who were admitted to our hospital from January 2020 to May 2022. The patients were divided into two groups, the observation group (total laparoscopic right-sided colon anastomosis, n=52) and the control group (laparoscopic plus auxiliary incision anastomosis, n=51), based on the different methods of surgical anastomosis. Various parameters were compared between the two groups, including surgical-related factors (operation time, anastomotic time, length of auxiliary incision, number of lymph nodes dissection, time of first postoperative anal exhaust, length of hospital stay), serum pain factors [nerve growth factor (NGF), prostaglandin E2 (PGE2), neuropeptide Y (NPY)], indicators of intestinal barrier function indicators [glutamine (Gln), diamine oxidase (DAO), D-lactic acid (DLA)], tumor clearance-related indicators (miR-192, miR-23a), pain intensity scores, and the incidence of complications (intestinal obstruction, anastomotic leakage, anastomotic stricture, anastomotic bleeding, incisional infection). [Results] There were no significant differences in operation time and number of lymph nodes dissection between the two groups (P > 0.05). The anastomosis time of observation group was longer than that of control group, and the length of auxiliary incision, the time of first postoperative anal exhaust and the length of hospital stay were shorter than that of control group (P<0.05). Before surgery, there were no significant differences in serum levels of NGF, PGE2, NPY, Gln, DAO and DLA between the two groups (P>0.05). On the 7th day after surgery, serum NGF, PGE2, NPY, DAO and DLA levels in both groups were higher than before surgery, but the observation group was lower than the control group; serum Gln level in both groups were lower than before surgery, but the observation group was higher than the control group (P<0.05). Before surgery, there were no significant differences in the expression levels of serum miR-192 and miR-23a between the two groups (P>0.05). On the 7th day after surgery, the expression level of serum miR-192 was higher than before surgery, and the level of miR-23a was lower than before surgery (P<0.05). However, there were no significant differences in the expression levels of serum miR-192 and miR-23a between the two groups (P>0.05). On the 1st, 3rd and 7th day after surgery, NRS scores in the observation group were lower than those in the control group, and the difference was statistically significant (P<0.05). The total incidence of complications in the observation group was lower than that in the control group in the first month after surgery (P<0.05). [Conclusion] Compared with laparoscopic plus auxiliary incision anastomosis, total laparoscopic right-sided colon anastomosis has obvious advantages in reducing surgical trauma, reducing postoperative serum pain factors, reducing pain degree and affecting intestinal barrier function, which can help shorten hospital stay, reduce complication rate and promote postoperative rehabilitation of patients.